'Click chemistry' synthesis of 1-(α-d-mannopyranosyl)-1, 2, 3-triazoles for inhibition of α-mannosidases. (10th April 2015) - Poláková, Monika; Stanton, Rhiannon; Wilson, Iain B.H.; Holková, Ivana; Šesták, Sergej; Machová, Eva; Jandová, Zuzana; Kóňa, Juraj
Abstract: Three new triazole conjugates derived fromd -mannose were synthesized and assayed in in vitro assays to investigate their ability to inhibit α-mannosidase enzymes from the glycoside hydrolase (GH) families 38 and 47. The triazole conjugates were more selective for a GH47 α-mannosidase (Aspergillus saitoi α1, 2-mannosidase), showing inhibition at the micromolar level (IC50 values of 50–250 μM), and less potent towards GH38 mannosidases (IC50 values in the range of 0.5–6 mM towards jack bean α-mannosidase or Drosophila melanogaster lysosomal and Golgi α-mannosidases). The highest selectivity ratio [IC50 (GH38)/IC50 (GH47)] of 100 was exhibited by the phenyltriazole conjugate. To understand structure-activity properties of synthesized compounds, 3-D complexes of inhibitors with α-mannosidases were built using molecular docking calculations. Graphical abstract: Highlights: d -Mannosyl triazoles for inhibition of α-mannosidases from the GH families 38 and 47. Triazoles were more efficient inhibitors towards α-mannosidase from the GH family 47. A selectivity ratio [IC50 (GH38)/IC50 (GH47)] of 100 for the most selective triazole. 3-D complexes (inhibitor-enzyme) were built using molecular docking calculations.